2016
DOI: 10.1371/journal.pone.0147741
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of a Child’s Built, Natural, and Social Environments to Their General Cognitive Ability: A Systematic Scoping Review

Abstract: The etiology of a child’s cognitive ability is complex, with research suggesting that it is not attributed to a single determinant or even a defined period of exposure. Rather, cognitive development is the product of cumulative interactions with the environment, both negative and positive, over the life course. The aim of this systematic scoping review was to collate evidence associated with children’s cognitive health, including inherent factors as well as chemical and non-chemical stressors from the built, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 284 publications
(443 reference statements)
0
44
1
Order By: Relevance
“…Many studies have separately demonstrated that environmental contaminants like air pollution and metals as well as early-life social and psychosocial factors, such as living in poverty and experiences of adversity, have independent and substantial effects on a range of child health outcomes including asthma, cognition and behavior, obesity, and perinatal risks like being born low birth weight [2][3][4][5]. Fewer studies have considered explicitly the accumulation of risk and potential synergies between social and environmental risks as determinants of child health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have separately demonstrated that environmental contaminants like air pollution and metals as well as early-life social and psychosocial factors, such as living in poverty and experiences of adversity, have independent and substantial effects on a range of child health outcomes including asthma, cognition and behavior, obesity, and perinatal risks like being born low birth weight [2][3][4][5]. Fewer studies have considered explicitly the accumulation of risk and potential synergies between social and environmental risks as determinants of child health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The onus of responsibility is on the researchers to represent limitations and bias within any study, along with potential variability across space and time and any potential uncertainty in measurements and modelling computations. Underlying biological mechanisms and confounding factors (e.g., gene variants, multiple exposures, poverty, poor nutrition, predisposing and enabling factors natural, built and social aspects) can provide the audience with a broader understanding of the complexity of certain health outcomes [53,59]. Certainly, attention must be paid to how we represent data and communicate the risks to the public [60].…”
Section: Discussionmentioning
confidence: 99%
“…The childhood well-being framework may aid in the identification of other stressors that can be related to prenatal exposure to recreational drugs [44]. A previous study examined contributing factors from the built, natural, and social environments that may be linked to prenatal exposure to recreational drugs [118]. Parental lifestyle factors, part of the social environment, are directly related to parental drug use during pregnancy.…”
Section: Exposure To Recreational Drugsmentioning
confidence: 99%
“…The desire to examine the synergistic effects of chemical and non-chemical stressors with inherent characteristics to gain a more comprehensive understanding of children's health outcomes is gaining momentum in the literature [44,118,147]. However, there is still a paucity of studies that examine these factors collectively.…”
Section: Linking Chemical and Non-chemical Stressors With Inherent Bimentioning
confidence: 99%